Predictors Associated With Post-Traumatic Hydrocephalus in Patients With Head Injury Undergoing Unilateral Decompressive Craniectomy - Hu, Qianxin; Di, Guangfu; Shao, Xuefei; Zhou, Wei; Jiang, Xiaochun (Frontiers in Neurology, 2018)
Objective: Post-traumatic hydrocephalus (PTH) is a common complication following decompressive craniectomy (DC) in patients with traumatic brain injury (TBI) and is associated with high risks of clinical deterioration and poor outcomes. Methods: Among TBI patients who underwent unilateral DC between January 2013 and December 2016, the clinical medical records, radiological variables on computed tomography (CT) scans, and development of hydrocephalus during the 3-month follow-up period after their injury were reviewed retrospectively. Results: Data from a total of 183 TBI patients who underwent unilateral DC were analyzed, and PTH was identified in 50 patients (27.32%) based on head CT scans. Univariate and multivariate analyses revealed that older age (P = 0.002), the Glasgow Coma Scale (GCS) score at admission (P  0.001), intraventricular hemorrhage (IVH; P = 0.008), post-traumatic cerebral infarction (PCI; P = 0.007), and postoperative meningitis (P = 0.016) were independent risk factors for the development of PTH after DC. Receiver operating characteristic curves were created and the areas under the curve (AUC) were calculated to further assess the accuracy of the variables for predicting PTH. The areas under the curve were 0.615 for age (95% confidence interval [CI]: 0.540–0.685), 0.715 for GCS score at admission (95% CI: 0.644–0.779), 0.596 for IVH (95% CI: 0.521–0.668), 0.601 for PCI (95% CI: 0.526–0.673), 0.542 for postoperative meningitis (95% CI: 0.467–0.616), and 0.836 for all five factors together (95% CI: 0.775–0.887). Conclusion: TBI patients who undergo unilateral DC with advanced age, lower GCS score at admission, coexisting IVH, PCI, and/or postoperative meningitis should be closely monitored at follow-up assessments for earlier prediction of PTH.